LIBERAL REFORMS OF THE FIRST HALF OF THE 1990'S AND THEIR IMPACT ON DAGESTAN ECONOMY - Muslimova, N T (History, Archeology and Ethnography of the Caucasus, 2016)
The author of the article makes an attempt to show the disruptive impact of liberal market reforms of the 1990s on the economy of Dagestan. Since 1995 most of the republic’s budget has been funded by the federal budget, and according to the author, this is largely due to the fact that the authorities of the republic did not take effective measures to create the national program of market reforms and the internal market.
Keywords: liberal reforms; privatization; corporatization; national program of market reforms; internal market.